log_e(x)loge(x) is commonly denoted as ln(x)ln(x), the natural log.
=>d/(dx) ln(x) = 1/x⇒ddxln(x)=1x
If you would like a proof, we can derive it from the limit definition:
lim_(delta x->0)(f(x+delta x)-f(x))/(delta x)
= lim_(delta x->0)(ln(x+delta x)-ln(x))/(delta x)
= lim_(delta x->0)(ln((x+delta x)/(x)))/(delta x)
= lim_(delta x->0)1/(delta x)ln(1+(delta x)/x)
= lim_(delta x->0)ln((1+(delta x)/x)^(1/(delta x)))
= lim_(delta x->0)ln((1+(delta x)/x)^(1/(delta x)))
"Let " tau equiv (delta x)/x:
= lim_(delta tau->0)ln((1+tau)^(1/(xtau)))
= lim_(delta tau->0)ln[((1+tau)^(1/(tau)))^(1/x)]
= ln[(e)^(1/x)]
= 1/x ln(e)
= 1/x (1)
= 1/x